Research of the object-oriented programming learning environment - Joana Lipeikienė; Kristina Kalpaitė; Aušra Kluonytė (Lietuvos Matematikos Rinkinys, 2002)
Research and results of the use of C++ Learning Environment for teaching at Vilnius Pedagogical University are described in this paper. Results of questionnaires and Web Ct statistical data were used for the research.